Education and affinity? pedagogies of sexual citizenship in LGBTIQ youth support videos. (7th February 2020) - Cover, Rob; Aggleton, Peter; Clarke, Kyra
ABSTRACT: This article provides an analysis of some of the ways in which educational resources for youth frame identity, sexuality and normativity within broader contexts of support and sexual citizenship. It focuses on online video resources for young people produced in Australia by the LGBTIQ support and curriculum advocacy organisation Safe Schools Coalition Australia and by the Minus18 Foundation. Developed as part of the larger All of Us educational package, these videos are explicitly pedagogical, presenting the viewer with 'real life' experiences from a range of young Australians. We consider the work the All of Us videos do in engaging with concepts of sexual citizenship, particularly as they seek to help young people navigate multiple forms of belonging and support. Of special interest is a series of tensions between normalising tendencies and the complexification of identities, communities, intimacies and belongings. While the videos may be perceived to operate within largely normative conceptualisations of sexuality, they explore ways of building affinity, peer support, and alternative ways of being that extend well beyond the logics usually offered by these frameworks.